Characteristics of Canadian Youth Adhering to Physical Activity and Screen Time Recommendations. (December 2021) - Fitzpatrick, Caroline; Burkhalter, Robin; Asbridge, Mark
The purpose of the study was to describe adherence to screen time (ST) and physical activity (PA) recommendations among Canadian youth. The present study was based on a representative sample of Canadian students from Grades 7 through 12 ( N = 47, 203). ST and PA as well as demographic (gender, ethnicity, grade, and province of residence) and individual (alcohol, tobacco and cannabis usage, school connectedness) correlates were self-reported by youth. In total, 49.2% (99% confidence interval [CI] = [46.3%, 52.2%]) of participants respected none of the recommendations, while 40.2% (99% CI [37.0%, 43.3%]) and 20.8% (99% CI [19.2%, 22.4%]) respected PA or ST recommendations, respectively. In terms of the correlates of health-related behavior, White ethnicity, alcohol use, and feeling more connected to school were positively correlated with adherence. Attending school in Quebec and smoking cannabis increased risk of poor compliance. The present findings may help the design of school-based health promotion strategies designed to increase PA and reduce ST.